Silica Fume Modified Cement-Based Mortar Exposed to High Temperatures: Residual Strengths and Microstructure (Journal of Engineering, 2023)
Several previous investigations and studies utilized silica fume (SF) or (micro silica) particles as supplementary cementitious material added as a substitute to cement-based mortars and their effect on the overall properties, especially on physical properties, strength properties, and mechanical properties. This study investigated the impact of the inclusion of silica fume (SF) particles on the residual compressive strengths and microstructure properties of cement-based mortars exposed to severe conditions of elevated temperatures. The prepared specimens were tested and subjected to 25, 250, 450, 600, and 900 °C. Their residual compressive strengths and microstructure were evaluated and compared with control samples (CS) subjected to similar conditions (the same temperature category). The outcomes indicated that including silica fume particles in mortar mixtures lowered the amount and width of microcracks, upgraded the mass-loss performance, lowered crystalline calcium hydroxide, and reinforced the cement paste, which explained the improvement in residual mechanical strengths.